2006
DOI: 10.1111/j.1467-9396.2006.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

An Extension of the Trade Restrictiveness Index to Large Economies*

Abstract: The Trade Restrictiveness Index (TRI) introduced by Anderson and Neary (1994 ) provided the first theoretically satisfying measure of a country's tariff structure by overcoming the problem of ad hoc specification of indexing weights and the related index number problem. We observe, however, that the TRI may not exist or may not be unique when countries are large. As a remedy, we propose a simple extension. Copyright � 2006 The Authors; Journal compilation � 2006 Blackwell Publishing Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Comparisons across the two measures have little meaning (i.e., one interpretation of Dakhlia and Temimi 2006), but we will demonstrate that comparisons within the measures across countries is a valuable tool for quantifying trade restrictiveness and its channels for policy analysis. In a related theoretical application of new trade theory, Costinot and Rodríguez-Clare (2014) find multiple TRIs.…”
Section: Calculating Welfare and Trismentioning
confidence: 93%
See 2 more Smart Citations
“…Comparisons across the two measures have little meaning (i.e., one interpretation of Dakhlia and Temimi 2006), but we will demonstrate that comparisons within the measures across countries is a valuable tool for quantifying trade restrictiveness and its channels for policy analysis. In a related theoretical application of new trade theory, Costinot and Rodríguez-Clare (2014) find multiple TRIs.…”
Section: Calculating Welfare and Trismentioning
confidence: 93%
“…This outcome is expected. Dakhlia and Temimi (2006) argue that, with large countries (i.e., upward sloping export supply), the definition of the TRI should be modified to acknowledge importer terms of trade gains. In context, Anderson and Neary (1996) originally define the TRI against free trade (as we are doing here).…”
Section: Calculating Welfare and Trismentioning
confidence: 99%
See 1 more Smart Citation
“…The weights in the average tariff measure are the actual import shares, whereas the weights in the TRI are the derivatives of the balance of trade function, which are not observable. However, Feenstra (1995Feenstra ( , 1562 has shown that, under the special assumption of linear demand, a simplified TRI can be expressed as: Dakhlia and Temimi (2006) note that the TRI is not uniquely defined for the large country case.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of this article evade an existence or uniqueness problem that arises with aggregation using the TRI in the large country case. Anderson and Neary (2005, Chapter 9) and Dakhlia and Temimi (2006) note that the TRI may not exist in the large country case, and where it exists it need not be unique. Essentially, the present methods, by using two different indices, are able to get both the domestic price aggregate (and hence quantity aggregate, the trade volume) right and the tariff revenue right (and hence real income right).…”
mentioning
confidence: 99%